Clinical Commentary: A Criteria-Based Testing Protocol for Return to Sport Post Hip Arthroscopy for Impingement - Gabriella Hugenberg; Jason Stallons; Chad Smith; Kathryn Brockhoff; Matthew Gingras; Darryl Yardley; Olufemi Ayeni; Mahmoud Almasri (International Journal of Sports Physical Therapy)
Overall, 84%-87% of athletes will return to sport following hip arthroscopy; however, some literature suggests that only 57% of athletes return to their preinjury level, and only 16.9% report optimal performance. This discrepancy may be due to a lack of consistency within the definition of return to sport as well as a lack of consistency within rehabilitation programs when determining return to sport readiness. Athletes who are returning to sport must demonstrate adequate range of motion, strength, and the ability to perform multi-directional movements without the risk of reinjury. There has yet to be a comprehensive, criteria-based, return to sport testing protocol that utilizes objective measures to ensure athletes are ready for return to sport.